Ischemic postconditioning influences electron transport chain protein turnover in Langendorff-perfused rat hearts - Cao, Song; Liu, Yun; Wang, Haiying; Mao, Xiaowen; Chen, Jincong; Liu, Jiming; Xia, Zhengyuan; Zhang, Lin; Liu, Xingkui; Yu, Tian (PeerJ, 2016)
Ischemia postconditioning (IPo) is a promising strategy in reducing myocardial ischemia reperfusion (I/R) injury (MIRI), but its specific molecular mechanism is incompletely understood. Langendorff-perfused isolated rat hearts were subjected to global I/R and received IPo in the absence or presence of the mitochondrial ATP-sensitive potassium channel (mitoKATP) blocker 5-hydroxydecanoate (5-HD). Myocardial mitochondria were extracted and mitochondrial comparative proteomics was analyzed. IPo significantly reduces post-ischemic myocardial infarction and improved cardiac function in I/R rat hearts, while 5-HD basically cancelled IPo’s myocardial protective effect. Joint application of two-dimensional polyacrylamide gel electrophoresis (2DE) and MALDI-TOF MS identified eight differentially expressed proteins between groups. Expression of cardiac succinate dehydrogenase (ubiquinone) flavoprotein subunit (SDHA) increased more than two-fold after I/R, while IPo led to overexpression of dihydrolipoyl dehydrogenase (DLD), NADH dehydrogenase (ubiquinone) flavoprotein 1 and isoform CRA_b (NDUFV1). When the mitoKATP was blocked, MICOS complex subunit Mic60 (IMMT) and Stress-70 protein (Grp75) were over expressed, while DLDH, ATPase subunit A (ATPA) and rCG44606 were decreased. Seven of the differential proteins belong to electron transport chain (ETC) or metabolism regulating proteins, and five of them were induced by closing mitoKATP in I/R hearts. We thus conclude that IPo’s myocardial protective effect relies on energy homeostasis regulation. DLD, SDHA, NDUFV1, Grp75, ATPA and rCG44606 may contribute to IPo’s cardial protective effect.
Keywords: Ischemia-reperfusion (I/R) injury; Mitochondrial ATP-sensitive potassium channel (mitoKATP); Energy homeostasis; Postconditioning; Comparative proteomics; Electron transport chain